Analisis Strategi Peningkatan Penerimaan Pajak Hiburan Pada Badan Pendapatan Daerah Kabupaten Bogor Tahun 2023 - Yusuf, Muhamad; Singgih, Rahadi Pratomo (Jurnal Ilmu Administrasi Publik, 2024)
Bogor Regency boasts beautiful natural landscapes and is supported by its natural potential, making it a highly favored tourist destination for both International and Domestic Tourists. Tourism plays an important role as it can be a leading sector in Economic Growth and Regional Income. In an effort to Increase Regional Tax Revenue, the issue faced by the Bogor Regency Government in tapping the potential Tax Revenue from the Entertainment sector is the suboptimal collection of Entertainment Tax, such as the Lack of Human Resources, and the Low Levels of Compliance and Payment Obligations from Taxpayers themselves. The research method used is descriptive with a qualitative approach. The researcher develops concepts and gathers facts, but does not test hypotheses. This study analyzes the Regional potential, then records the targets and realizations of Regional Tax Revenue, as well as the collection related to Regional Taxes during the observation year. Entertainment Tax plays a significant role according to its development. Therefore, the Local Government can make the Entertainment business one of the potential sources to be taxed. Areas that have the potential to Increase Entertainment Tax Revenue are those that have tourist attractions and also contain Entertainment businesses. The strategy to Increase Entertainment Tax Revenue at the Regional Revenue Agency of Bogor Regency has been running well, which includes the Regional Civil Service Agency forming an intensification and extensification collection team. The Regional Civil Service Agency has improved the work skills and knowledge of employees by providing guidance and training to employees as an effort to increase the competence of Tax Officers